1997
DOI: 10.1046/j.1570-7458.1997.00155.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial changes in aphid and parasitoid populations following applications of deltamethrin in winter wheat

Abstract: The spatial and temporal effects of the pyrethroid insecticide, deltamethrin, on populations of cereal aphids and their primary parasitoids and hyperparasitoids were investigated in a large scale field experiment in winter wheat. Four hectare plots were treated at the recommended field concentration or a reduced concentration representing one twentieth of field rate. A control plot was left unsprayed. Invertebrate populations were sampled at sites within a grid layout covering the whole plots, enabling the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 23 publications
1
37
0
1
Order By: Relevance
“…The less persistent pesticides, abamectin and trichlorfon, whose effects last less than five days are likely to have less impact on the population of the natural enemy in the field compared to the persistent phosmet easily allowing the ''vertical colonisation'' via emergence of treated cocoons [a high degree of protection against all the insecticides tested was provided by the silken cocoon, as previously stated by Medina et al (2001)], as well as ''horizontal colonisation'' from the reinvasion of the depleted areas from the undepleted surroundings, with a similar pattern to that described by Longley et al (1997) in the case of aphids parasitoids in winter wheat crops treated with deltamethrin.…”
Section: Discussionmentioning
confidence: 57%
“…The less persistent pesticides, abamectin and trichlorfon, whose effects last less than five days are likely to have less impact on the population of the natural enemy in the field compared to the persistent phosmet easily allowing the ''vertical colonisation'' via emergence of treated cocoons [a high degree of protection against all the insecticides tested was provided by the silken cocoon, as previously stated by Medina et al (2001)], as well as ''horizontal colonisation'' from the reinvasion of the depleted areas from the undepleted surroundings, with a similar pattern to that described by Longley et al (1997) in the case of aphids parasitoids in winter wheat crops treated with deltamethrin.…”
Section: Discussionmentioning
confidence: 57%
“…By contrast, Ruggle & Holst (1995) studied a 60 m by 40 m area within a winter wheat field and concluded that aphids were concentrated in the centre of the field when population levels were high. Longley et al (1997) studied the spatial and temporal distribution of aphids and parasitoids following insecticide application in winter wheat in the UK whilst Schotzko & Smith (1991) demonstrated that the host plant (winter wheat) itself may influence aphid distributions.…”
Section: Introductionmentioning
confidence: 99%
“…This dynamic has been particularly well documented under laboratory conditions (Waage et al 1985). When recolonizing a crop after insecticide treatment, parasitoids may return to depleted areas (where insecticide treatments have been done) from undepleted surroundings (Longley et al 1997), a process called "horizontal recruitment." In addition, a process of "vertical recruitment" of parasitoids (i.e., the emergence of adults from mummies) may occur in the treated crop.…”
mentioning
confidence: 99%
“…For example, pest resurgence or an increase in populations of secondary pests can occur as a result of the death or perturbation of beneÞcial arthropods by pesticides (Hardin et al 1995, Longley et al 1997. Parasitoids can be exposed to insecticides through spray droplets (Jepson 1989), through residues on the crop foliage when foraging (Brown 1989;Jepson 1989;Longley and Jepson 1996a,b), or when feeding on contaminated water droplets, nectar, or honeydew (Longley and Stark 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation